Do post-tonsillectomy patients who report bleeding require observation if no bleeding is present on exam?. (April 2017) - Yuen, Sonia; Kawai, Kosuke; Roberson, David W.; Murray, Ryan
Abstract: Objective: Three to ten percent of tonsillectomy patients experience post-tonsillectomy hemorrhage. Examination of those patients who return to the Emergency Department (ED) with a history of hemorrhage may be found to have active bleeding, a coagulum within the fossa, or a normal post-operative exam. It is not known if those with a normal postoperative exam require inpatient observation. Methods: This is a retrospective series from 1/1/2010 to 12/31/2014 at a tertiary pediatric hospital. We evaluated outcomes in patients who presented to our ED with a history of post tonsillectomy hemorrhage, but after a thorough inspection failed to demonstrate active bleeding or clot, and were thus deemed to have a normal postoperative exam. This cohort was then evaluated for subsequent active bleeding requiring cauterization. Demographics and clinical data were extracted from the medical record. Results: In 337 visits with a history of bleeding, and a normal postoperative exam, 38 (11%) subsequently bled requiring cauterization. 32/38 (84%) bled within 24 h of admission to the ED. No demographic or clinical variables predicted an increased risk of bleeding during observation. Conclusions: Eleven percent of patients who presented to the ED with a history of bleeding at home but a normal postoperative exam subsequently bled and required cautery, usually within 24 h. Aside from the history of bleeding at home, we found no additional predictors of subsequent bleeding and recommend this group of patients should be considered for 24 hour in-hospital observation prior to discharge.